Comparative Analysis of The Political Motivation of The Partisans Who Vote for D. Trump and V. Zelensky - Max Ratnikov; Natalia Zemzyulina (The Journal of Society and Media, 2020)
The aim of this article was to reveal the motivation of partisan who vote for showmen which were elected to high government posts. Data collection was carried out using a combination of quantitative and qualitative methods. In the first case, a questionnaire (100 questionnaires) was used, in which people who had reached the voting age and voted for Zelensky and his party in the elections participated, followed by an in-depth interview. The study participants were recruited from different districts of the city of Cherkasy. As a result, the common and different in the electorate of D. Trump and V. Zelensky was revealed.